FUTURES on Air: Community radio and public engagement. Issue 1 (1st April 2021) - Watson, Rob
FUTURES on Air was a public engagement project delivered as part of FUTURES2020, a European Researchers' Night event, which consisted of a series of co-produced radio conversations between community programme makers and researchers, which was broadcast across stations in the southwest of England, November 2020. FUTURES on Air explored the role of community media, specifically community radio, in relation to alternative forms of public engagement with researchers, and as impacted by the COVID-19 pandemic.